Construction of unique SCF3-containing building blocks via allylic alkylation of Morita-Baylis-Hillman adducts - Halder, Priyanka; Pol, Mahesh D.; Ahire, Milind M.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2020)
Lewis base-catalyzed allylic alkylation of Morita-Baylis-Hillman adducts with alpha-SCF3 ketones has been demonstrated. The developed strategy provides efficient access to a series of highly functionalized scaffolds featuring trifluoromethanesufinyl motif on a stereogenic carbon.

Annulation of enals with carbamoylpropiolates via NHC-catalyzed enolate pathway: access to functionalized maleimides/iso-maleimides and synthesis of aspergillus FH-X-213 - Viveki, Amol B.; Pol, Mahesh D.; Halder, Priyanka; Sonavane, Sameer R.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2021)
Herein we report the N-heterocyclic carbene (NHC)-catalyzed [3 + 2] annulation of alpha,beta-unsaturated aldehydes with carbamoylpropiolates via an unusual enolate pathway leading to the construction of highly functionalized maleimides or isomaleimides. The electronic effect imposed by the alkyl/aryl group present on the amide nitrogen of carbamoylpropiolates plays a crucial role in the selective formation of these important five-membered heterocyclic building blocks. The developed protocol is mild and tolerates a wide range of substituents on both substrates. The application of this protocol in the synthesis of the antibacterial natural product Aspergillus FH-X-213 has also been demonstrated.

PIDA-mediated N-N bond formation to access pyrazolidine-3,5-diones: a novel process for uricosuric agents G-25671 and sulfinpyrazone - Halder, Priyanka; Mhaske, Santosh B. (Chemical Communications, 2023)
Traditionally, toxic and expensive hydrazine building blocks are required to construct pharmaceutically important pyrazolidine-3,5-diones. Herein, we have described a novel method for their synthesis based on metal-free oxidative dehydrogenative N-N bond formation by PIDA-mediated reaction of easily accessible dianilide precursors. The developed mild reaction protocol features a good functional group tolerance and scalability. The application of this method is demonstrated by offering a unique route for the synthesis of uricosuric agents G-25671 and sulfinpyrazone from inexpensive starting material aniline via smooth functionalization of the well-designed diversity-oriented cyclopropyl key intermediate.